Liquidity in resolution: Comparing frameworks for liquidity provision across jurisdictions - Sebastian Grund; Nele Nomm; Florian Walch (European Central Bank (ECB), 2020)
As a response to the global financial crisis that started in 2008, many countries established dedicated resolution regimes that seek to limit the use of taxpayer money while maintaining the functions of failing banks that are critical for financial stability. This paper extends the existing research by zooming in on the specific topic of liquidity provision to banks in resolution. It examines the provision of liquidity in the United States, the United Kingdom, Japan, Canada and the banking union of the European Union (thereafter: the "banking union"). The paper observes the differences and commonalities of policy choices across jurisdictions with regard to both the relationship between private prefunding and temporary public liquidity provision and the roles of the public budget and the central bank. The comparison also reveals that the role of fiscal authorities is strong and that guarantees from a public budget are a common feature. The framework for the provision of liquidity in the banking union is not yet complete as the construction of a public sector backstop of sufficient size and speed is comparatively more complex in the banking union than in other jurisdictions. Therefore, the idea of establishing a European-level guarantee framework - which would allow access to Eurosystem liquidity for banks coming out of resolution with limited collateral - is being further investigated.
Keywords: G01; G21; G28; G33; E58; 330; European Central Bank; liquidity; resolution; banking union